Characterization of a Type‐2 Diacylglycerol Acyltransferase from Haematococcus pluvialis Reveals Possible Allostery of the Recombinant Enzyme. Issue 5 (26th December 2019) - Nguyen, Trinh; Xu, Yang; Abdel‐Hameed, Mona; Sorensen, John L.; Singer, Stacy D.; Chen, Guanqun
Abstract: Haematococcus pluvialis is a green microalga used in the algal biotechnology industry that can accumulate considerable amounts of storage triacylglycerol (TAG) and astaxanthin, which is a high‐value carotenoid with strong antioxidant activity, under stress conditions. Diacylglycerol acyltransferase (DGAT) catalyzes the last step of the acyl‐CoA‐dependent TAG biosynthesis and appears to represent a bottleneck in algal TAG formation. In this study, putative H. pluvialis DGAT2 cDNA ( HpDGAT2A, B, D and E ) were identified from a transcriptome database and were subjected to sequence‐based in silico analyses. The coding sequences of HpDGAT2B, D, and E were then isolated and characterized through heterologous expression in a TAG‐deficient Saccharomyces cerevisiae strain H1246. The expression of HpDGAT2D allowed the recovery of TAG biosynthesis in this yeast mutant, and further in vitro enzymatic assays confirmed that the recombinant HpDGAT2D possessed strong DGAT activity. Interestingly, the recombinant HpDGAT2D displayed sigmoidal kinetics in response to increasing acyl‐CoA concentrations, which has not been reported in plant or algal DGAT2 in previous studies.